2014
DOI: 10.1111/ijd.12135
|View full text |Cite
|
Sign up to set email alerts
|

Adult pityriasis lichenoides‐like mycosis fungoides: a clinical variant of mycosis fungoides

Abstract: In patients with clinical features of longstanding PL and histological findings consistent with MF, differential diagnosis must include PL, LyP, and papular MF. As some forms of PL evolve towards MF and PL-like forms of MF, these patients should undergo regular follow-up and repeated biopsies in order to discard diagnoses of atypical forms of MF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…PL and PL-like MF have been described as having similar clinical and histological findings. Three of four patients were initially diagnosed with PL based on their clinical and histological associations; however, additional histological tests confirmed that they had PL-like MF 6 . The important clinical differentiation between PL and PL-like MF is that PL spontaneously heals within several months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PL and PL-like MF have been described as having similar clinical and histological findings. Three of four patients were initially diagnosed with PL based on their clinical and histological associations; however, additional histological tests confirmed that they had PL-like MF 6 . The important clinical differentiation between PL and PL-like MF is that PL spontaneously heals within several months.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial that PL-like lesions are differentiated from those of PL, papular MF, and lymphomatoid papulosis (LyP) using histology. de Unamuno Bustos et al 6 reported that PL, PL-like MF, papular MF, and LyP all produce papular lesions with histological MF patterns ( Table 4 ). PL and PL-like MF have been described as having similar clinical and histological findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu lezyonlar MF'den oldukça farklı bir seyir gösterdi. Hastamızdaki iki nadir hastalık birlikteliğinin rastlantısal bir durum mu yoksa anlamlı mı olduğunu araştırdığımızda literatürde az sayıda olguda bu iki hastalığın bir arada olduğunu; ancak bunların homojen bir grup oluşturmadığını belirledik(2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Tüm bu olguları ve bizim hastamızı bir arada değerlendirdiğimizde aradaki ilişkinin dört grup şeklinde sınıflandırılabileceği görüşündeyiz.…”
unclassified